Functional–Structural Plant Models Mission in Advancing Crop Science: Opportunities and Prospects - Soualiou, Soualihou; Wang, Zhiwei; Sun, Weiwei; de Reffye, Philippe; Collins, Brian; Louarn, Gaëtan; Song, Youhong (Frontiers in Plant Science, 2021)
Functional-structural plant models (FSPMs) have been evolving for over two decades, and their future development, to some extent, depends on the value of potential applications in crop science. To date, stabilising crop production by identifying valuable traits for novel cultivars adapted to adverse environments is topical in crop science. Thus, this review will examine how FSPMs are able to address new challenges in crop science for sustainable crop production. FSPMs developed to simulate organogenesis, morphogenesis and physiological activities under various environments, are amenable to downscale to the tissue, cellular, molecular level, or upscale to the whole plant and ecological level. A modelling framework with independent and interactive modules, advanced algorithms provides morpho-physiological details at various scales. FSPMs are shown able to (i) provide crop ideotypes efficiently for optimising the resource distribution and use for greater productivity and less disease risk; (ii) guide molecular design breeding via linking molecular basis to plant phenotypes, as well as enrich crop models with an architectural dimension to assist breeding; and (iii) interact with plant phenotyping for molecular breeding in embracing 3D architectural traits. This review illustrates that FSPMs have great prospects in speeding up precision breeding for specific environments due to the capacity for guiding and integrating ideotypes, phenotyping, molecular design, and linking molecular basis to target phenotypes. Consequently, the promising great applications of FSPMs in crop science will, in turn, accelerate their evolution, and vice versa.